Creation of the Economic Security of State: National Core Competence - Jaroslaw GRYZ; Aneta NOWAKOWSKA-KRYSTMAN (Revista de Management Comparat International)
The debate about the meaning and significance of creation of the economic security of state has different dimensions. The interpretation occupies a central place in critical security studies focusing on theoretical and empirical studies concerning national core competence. However, is not always clear from these studies what crates a certain explanations. The article elaborates earlier formulated proposal to treat the concept of economic security as a part of strategic security management. It aims to make a contribution on certain concepts of economic security through a variety of forms interconnected in security studies and competence of state structures in shaping social environment. The purpose of this article is to determine the theoretical basis for the design of state security as well as their practical, utilitarian application in the activities of state institutions to ensure the safety and progress based on economy.